Cicero's use of judicial theater - Hall, Jon (Jon C. R.), 1961- (University of Michigan Press, 2014)
"In Cicero's Use of Judicial Theater, Jon Hall examines Cicero's use of showmanship in the Roman law-courts, looking in particular at the nonverbal devices that he employs during his speeches as he attempts to manipulate opinion. Cicero's speeches in the law-courts often incorporate theatrical devices including the use of family relatives as props during emotional appeals, exploitation of tears and supplication, and the wearing of specially dirtied attire by defendants during a trial, all of which contrast strikingly with the practices of the modem advocate. Hall investigates how Cicero successfully deployed these techniques and why they played such a prominent part in the Roman courts. These "judicial theatrics" are rarely discussed by the ancient rhetorical handbooks, and Cicero's Judicial Theater argues that their successful use by Roman orators derives largely from the inherent theatricality of aristocratic life in ancient Rome--most of the devices deployed in the courts appear elsewhere in the social and political activities of the elite. While Cicero's Judicial Theater will be of interest primarily to professional scholars and students studying the speeches of Cicero, its wider analyses, both of Roman cultural customs and the idiosyncratic practices of the law-courts, will prove relevant also to social historians, as well as historians of legal procedure"--